The Status–Health Paradox: Organizational Context, Stress Exposure, and Well-being in the Legal Profession. (March 2018) - Koltai, Jonathan; Schieman, Scott; Dinovitzer, Ronit
Prior research evaluates the health effects of higher status attainment by analyzing highly similar individuals whose circumstances differ after some experience a "status boost." Advancing that research, we assess health differences across organizational contexts among two national samples of lawyers who were admitted to the bar in the same year in their respective countries. We find that higher-status lawyers in large firms report more depression than lower-status lawyers, poorer health in the American survey, and no health advantage in Canada. Adjusting for income exacerbates these patterns—were it not for their higher incomes, large-firm lawyers would have a greater health disadvantage. Last, we identify two stressors in the legal profession, overwork and work–life conflict, that are more prevalent in the private sector and increase with firm size. Adjusting for these stressors explains well-being differences across organizational contexts. This study documents the role of countervailing mechanisms in health inequality research.